YT521-B homology domain family proteins as N6-methyladenosine readers in tumors - Yang, Heng; Chiang, Chengyao; Luo, Qinhong; Chen, Chunlan; Huang, Junrong; Zhu, Lizhi; Zheng, Duo (Frontiers in Genetics, 2022)
N6-methyladenosine (m6A) is the most abundant internal mRNA modification in eukaryotes and plays diverse roles in gene regulation. The m6A modification plays a significant role in numerous cancer types, including kidney, stomach, lung, bladder tumors, and melanoma by varied mechanisms. As direct m6A readers, the YT521-B homology domain family proteins (YTHDFs) play a key role in tumor transcription, translation, protein synthesis, tumor stemness, immune escape, epithelial-mesenchymal transition (EMT) and chemotherapy resistance. An in-depth understanding of the molecular mechanism of YTHDFs is expected to provide new strategies for tumor treatment. In this review, we provide a systematic description of YTHDF protein structure and their function in tumor progression.